2022
DOI: 10.1172/jci153157
|View full text |Cite
|
Sign up to set email alerts
|

LC3-associated phagocytosis in bone marrow macrophages suppresses acute myeloid leukemia progression through STING activation

Abstract: The bone marrow (BM) microenvironment regulates acute myeloid leukemia (AML) initiation, proliferation and chemotherapy resistance. Following cancer cell death, a growing body of evidence suggests an important role for remaining apoptotic debris in regulating the immunologic response to, and growth of, solid tumors. Here we investigated the role of macrophage LC3-associated phagocytosis (LAP) within the BM microenvironment of AML.Depletion of BM macrophages increased AML growth in-vivo. We showed that LAP is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 88 publications
0
40
1
Order By: Relevance
“…One potential clue was the observation that LAP deficiency resulted in the recruitment and activation of cytotoxic T cells in solid tumor models, which could restrain tumor expansion ( 11 ). In the study by Moore and colleagues, LAP deficiency increased CD4 + Th cells in one AML model (MN1), although, unlike prior solid tumor studies, there was no recruitment of cytotoxic CD8 + cells ( 10 ). The authors also found that AML cells promoted the expansion of both tumor-associated macrophages and resident BM macrophages, and neither of these processes was altered when LAP was impaired ( 10 ).…”
Section: Lap Restricts Aml Expansionmentioning
confidence: 80%
See 4 more Smart Citations
“…One potential clue was the observation that LAP deficiency resulted in the recruitment and activation of cytotoxic T cells in solid tumor models, which could restrain tumor expansion ( 11 ). In the study by Moore and colleagues, LAP deficiency increased CD4 + Th cells in one AML model (MN1), although, unlike prior solid tumor studies, there was no recruitment of cytotoxic CD8 + cells ( 10 ). The authors also found that AML cells promoted the expansion of both tumor-associated macrophages and resident BM macrophages, and neither of these processes was altered when LAP was impaired ( 10 ).…”
Section: Lap Restricts Aml Expansionmentioning
confidence: 80%
“…Further, infusion of ex vivo–expanded NK cells together with the allograft improves outcomes ( 9 ). As demonstrated by Moore et al ( 10 ), another exciting therapeutic strategy centers on modulating macrophage activity within the leukemia TME. In solid tumors, tumor-associated macrophages (TAMs) are composed of different cell populations that can either repress or foster tumor growth ( 11 , 12 ).…”
Section: The Microenvironment In Regulating Tumor Progressionmentioning
confidence: 99%
See 3 more Smart Citations